Analysis of real‐world capillary blood glucose data to help reduce HbA1c and hypoglycaemia in type 1 diabetes: Evidence in favour of using the percentage of readings in target and coefficient of variation. Issue 2 (20th October 2022) - Eissa, Mohammad R.; Benaissa, Mohammed; Good, Tim; Hui, Zheng; Gianfrancesco, Carla; Ferguson, Carolin; Elliott, Jackie
Abstract: Aims: To examine real‐world capillary blood glucose (CBG) data according to HbA1c to define proportions of CBG readings at different HbA1c levels, and evaluate patterns in CBG measurements to suggest areas to focus on with regard to self‐management. Methods: A retrospective analysis stratified 682 adults with type 1 diabetes split into quartiles based on their HbA1c . The proportions of results in different CBG ranges and associations with HbA1c were evaluated. Patterns in readings following episodes of hyperglycaemia and hypoglycaemia were examined, using glucose to next glucose reading table (G2G). Results: CBG readings in the target range (3.9‐10 mmol/L) increase by ~10% across each CBG quartile (31% in the highest versus 63% in the lowest quartile, p  < 0.05). The novel G2G table helps the treatment‐based interpretation of data. Hypoglycaemia is often preceded by hyperglycaemia, and vice‐versa, and is twice as likely in the highest HbA1c quartile. Re‐testing within 30 min of hypoglycaemia is associated with less hypoglycaemia, 1.6% versus 7.2%, p  < 0.001, and also reduces subsequent hyperglycaemia and further hypoglycaemia in the proceeding 24 h. The coefficient of variation, but not standard deviation, is highly associated with hypoglycaemia, r = 0.71, and a CV ≤ 36% equates to 3.3% of CBG readings in the hypoglycaemic range. Conclusions: HbA1c <58 mmol/mol (7.5%) is achievable even when only ~60% of CBG readings are between 3.9–10 mmol/L. Examining readings subsequent to out‐of‐range readings suggests useful behaviours which people with type 1 diabetes could be supported to adhere to, both in a clinic and structured education programmes, thereby decreasing the risk of hypoglycaemia whilst also reducing hyperglycaemia and improving HbA1c .